Zpráva o konferenci Cesty k národnímu obrození: běloruský a český model - Ivanova, Alena (Lidé města, 2006)
An international scientific conference “The ways to national revival: Byelorussian and Czech models” was held on July 4 through July 6, 2006, at the Faculty of Humanities of the Charles University in Prague. The conference was organized by the Faculty of Humanities in collaboration with the Institute of Slavic and Eastern European Studies at the Philosophical Faculty of the Charles University. The international conference project was supported by the Ministry of Foreign Affairs of the Czech Republic as part of the transformation collaboration. Byelorussian, Czech, German, Polish, and Lithuanian scientists and academicians who are professionally engaged in the topic of Byelorussian national revival, in historical and linguistic context, were invited to participate at the conference. The Byelorussian – Czech conference, devoted to problems of national and cultural revival of both of these nations has contributed to research of historical national development of European countries. The conference touched upon problems of creationprocesses of the Byelorussian and Czech national movements in the 19th and 20th centuries: The Byelorussian national movement under Russian and Polish double influence resulting in creation of BSSR as part of the USSR; the Czech cultural revival that was under the German influence and later grew into the concept of Czechoslovakism and Byelorussian national revival considered to be a delayed version of nationalism of the 90’s of the 20th century.